Altern und Altersvorsorge in einer frühen Hochkultur - Maul, Stefan M. (Altern: Biologie und Chancen, 2022)
Although the average life expectancy was drastically lower than today because of the enormously high child mortality rate, there were old people in need of care in the ancient Near East. The following shows the means by which provision for old age was ensured, especially when there was a lack of children willing to care.
Gesehen am 25.07.2022
Keywords: Assyrien